Red Line Diffuse‐Like Aurora Driven by Time Domain Structures Associated With Braking Magnetotail Flow Bursts - Yangyang Shen; Jun Liang; Anton Artemyev; Vassilis Angelopoulos; Qianli Ma; Larry Lyons; Jiang Liu; Yukitoshi Nishimura; Xiao‐Jia Zhang; Ivan Vasko; Donald L. Hampton (Geophysical Research Letters, 2024)
Abstract Magnetotail earthward‐propagating fast plasma flows provide important pathways for magnetosphere‐ionosphere coupling. This study reexamines a flow‐related red‐line diffuse‐like aurora event previously reported by Liang et al. (2011, https://doi.org/10.1029/2010ja015867), utilizing THEMIS and ground‐based auroral observations from Poker Flat. We find that time domain structures (TDSs) within the flow bursts efficiently drive electron precipitation below a few keV, aligning with predominantly red‐line auroral intensifications in this non‐substorm event. The diffuse‐like auroras sometimes coexisted with or potentially evolved from discrete forms. We forward model red‐line diffuse auroras due to TDS‐driven precipitation, employing the time‐dependent TREx‐ATM auroral transport code. The good correlation (∼0.77) between our modeled and observed red line emissions underscores that TDSs are a primary driver of the red‐line diffuse‐like auroras, though whistler‐mode wave contributions are needed to fully explain the most intense red‐line emissions.